2021
DOI: 10.1021/acsami.0c18861
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Carbon Dioxide-Selective Composite Membrane Containing a γ-CD-MOF Layer

Abstract: Mixed matrix membranes (MMMs) for CO 2 separation have overcome the trade-off between gas permeability and gas selectivity to some extent. However, most MMMs still are prepared in lab-and pilot-scales since the permeability and selectivity of CO 2 are not good enough to reach the economically available requirements. Moreover, the fabrication of few MMMs with good separation performance is time-consuming or need harsh conditions. In this study, a novel MOF-based composite membrane (PANγ-CD-MOF-PU membrane) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Apart from the storage of single target compounds, CD-MOF based materials also show high potential in the selective separation of gases, hydrocarbons, isomers, benzenoid compounds and other mixtures. 90,101,158,159,169,[205][206][207][208] Thanks to the tailorable pore sizes and uncoordinated, weakly nucleophilic primary hydroxyl groups of CD-MOFs they could be significant even in large-scale industrial processes, for instance during acetylene (C 2 H 2 ) gas synthesis where minor fractions of CO 2 are formed as a side-product. To remove trace amounts of CO 2 from a mixture with C 2 H 2 , Li et al synthesized a K-and a Rb-g-CD-MOF which showed inverse adsorption abilities.…”
Section: Storage Separation and Removal Of Chemicalsmentioning
confidence: 99%
“…Apart from the storage of single target compounds, CD-MOF based materials also show high potential in the selective separation of gases, hydrocarbons, isomers, benzenoid compounds and other mixtures. 90,101,158,159,169,[205][206][207][208] Thanks to the tailorable pore sizes and uncoordinated, weakly nucleophilic primary hydroxyl groups of CD-MOFs they could be significant even in large-scale industrial processes, for instance during acetylene (C 2 H 2 ) gas synthesis where minor fractions of CO 2 are formed as a side-product. To remove trace amounts of CO 2 from a mixture with C 2 H 2 , Li et al synthesized a K-and a Rb-g-CD-MOF which showed inverse adsorption abilities.…”
Section: Storage Separation and Removal Of Chemicalsmentioning
confidence: 99%
“…Kang et al [ 20 ] found that the 1,2–bi–(4–pyridyl) ethylene (BPE) molecule distributed in channels can improve the H 2 /CO 2 separation performance of the [Ni 2 ( L –asp) 2 (BPE)]·(G) membrane. Under a two-step coating process, a new MOF-based membrane (PAN– γ –CD–MOF–PU membrane) was fabricated by Fan et al [ 21 ], with a permeability to CO 2 of over 70 barrer and selectivity to CO 2 /N 2 and CO 2 /O 2 of 253.46 and 154.28, respectively. Yan et al [ 22 ] synthesized a UiO–66 membrane through tertiary growth at room temperature, which exhibited an optimal selectivity of 37.8 for CO 2 /N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Different alkali metal ions including K + , Li + , or Rb + can be used to construct γ‐CD‐MOFs with a similar extended structure 44,45 . Because of its porous structure, rich hydroxyl groups and biocompatibility, γ‐CD‐MOF has important applications in the fields of gas adsorption and separation, 46–51 biomedicine, 52 and sensing 53,54 . However, these applications are currently faced with severe challenges originating from the powder state and poor humidity stability of γ‐CD‐MOF.…”
Section: Introductionmentioning
confidence: 99%